Vector-Borne Diseases Recent Developments in Epidemiology and Control - Claborn, David; Bhattacharya, Sujit; Roy, Syamal (IntechOpen, 2020)
Vector-Borne Diseases - Recent Developments in Epidemiology and Control utilizes the unique capabilities of open-access publishing to share exciting developments in the biology, diagnosis, and treatment of diseases spread by arthropods. From malaria to dengue to leishmaniasis, the diseases addressed in this book continue to present threats to the life and well-being of millions around the world. The international cast of writers published here provide specific insight into a full spectrum of diseases spread by insects and their close relatives.